El programa minimista en la teoria de principis i paràmetres - Picallo, M. Carme (Caplletra. Revista Internacional de Filologia, 2004)
This paper intends to offer a general overview of the ideas that have been proposed in generative grammar in the last decade. The theoretical framework that supports them is summarized (the Principles and Parameters theory) and we explain some conceptual changes that the theory has undergone from its first formulation (known as the Government and Binding model) to the recent proposals (known as the Minimalist model). The changes introduced under the minimalist perspective obbey to the necessity of eliminating some theoretical artifacts by submitting to scrutiny some assumptions. The Minimalist view suggests that the only possible grammatical operations are the unavoidable ones that are triggered by the interaction of the linguistic system with other external systems.